Spremembe porabe kisika med obremenitvijo - Fležar, Matjaž (Medicinski razgledi, 2002)
Exercise - the performance of muscle work - requires intact functional recruitment of the ventilatory, cardiovascular and muscular systems. The mechanisms leading to an increase in oxygen consumption during exercise are described. The oxygen status of the body is divided into various functional steps of oxygen transport and pathological mechanisms of oxygen transfer occurring at different levels of transport. Oxygen consumption mechanisms during exercise at high altitude are also described.
Keywords: Altitude; Kisik, poraba; Napor; Exertion; Oxygen Consumption; Višina (nadmorska); fiziologija; kisik; poraba; nadmorska višina